FEDERAL SUPPORT OF SCIENTIFIC INQUIRY IN THE UNITED STATES: CURRENT EVOLUTION UNDER THE POLITICAL STRUGGLE - I. A. Istomin (Сравнительная политика)
2000’s and 2010’s witnessed diminishing margin of the United States in science and technology. Meanwhile, the U.S. remains a clear leader in this fi eld. Major driving force of the country’s success in the second half of the ХХ century remained assertive federal science policy. The article seeks to identify major trends in evolution of the U.S. science policy and the reasons behind relative decline of the level of budget support of the scientifi c research. The author studies evolution of the policies of George Bush and Barack Obama, as well as the views of Democrats and Republicans in the House of Representatives and the Senate. The article also examines the input into the federal policy of the governmental bodies, which are directly responsible for its implementation, as well as non-governmental organizations, which seek to advocate interests of scientists; it studies rising competition between the executive authorities and legislators for the recognition as a major champion of the academic community as well as American Recovery and Reinvestment Act.